The Komunikasi Persuasi Busa Pustaka Dalam Meningkatkan Ondeks Pembangunan Literasi Masyarakat Lampung: Komunikasi Persuasi Busa Pustaka - Putri, Anggraini; Eko, Ade Eko Setiawan; Kartika, Tina (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2025)
This study aims to determine, analyze and understand the extent to which the persuasion communication strategy of Library foam in improving the Literacy Development Index of Lampung community. This type of research is a qualitative descriptive research. Based on the results of interviews and documentation research shows that the strategy undertaken by Busa Pustaka in increasing the Literacy Development Index of Lampung community based on the Elaboration Likelihood (ELM) Model. Where first, the concept presented by Busa Pustaka by attracting the interest of the public or children through Mario animated costumes. This can provide a message, creative and innovative touch to visitors and create an interesting and inspiring learning environment. Second, the Busa Pustaka community uses advertisements that are spread through social media. This can provide a message to readers in order to increase awareness of reading books and also provide information regarding the programs of library foam activities. Keywords: Library Foam, Community Literacy Development Index, Persuasion Communication